"I Think There Should Be Photos": Female Indoor Tanners' Perceptions of Health Warning Labels for Tanning Beds. Issue 11 (19th September 2022) - Gosselin, Sydney; McWhirter, Jennifer E.; Mutti-Packer, Seema; McEwen, Scott A.; Papadopoulos, Andrew; Rosen, Cheryl F.; Beecker, Jennifer
ABSTRACT: This study explores female indoor tanners' perceptions of the current, text-only Canadian health warning label (HWL) for tanning equipment, as well as pictorial, evidence-based alternative HWLs. We created 10 test HWLs that depicted skin health effects, eye damage, premature aging, and death. Young women who had tanned indoors in the past year discussed these and the current federal HWL in focus groups. Although the current Canadian HWL was seen as informative, several participants did not recognize it, and many said that they would not read it due to the small text, wordiness, and lack of an image. Graphic images, particularly those depicting permanent conditions affecting the face, eyes, or appearance, were seen as effective. Common criticisms of the images were lack of believability, relatability, and comprehensibility. Although concise text was important for encouraging reading, many participants expressed a desire for more information in the test HWLs. Premature aging was of great concern to many participants, but the images selected for these HWLs were not perceived as effective. Although the text was seen as effective in the death HWLs, most participants dismissed the images. This research has implications for IT HWLs in Canada and globally. These results suggest that graphic images may be impactful in IT HWLs. Images must be supplemented with informative text that increases believability, relatability, and comprehensibility. These modifications would create HWLs that are engaging, informative, and that form part of a wider effort to spread awareness about the harmful effects of IT.